Prevalence of Post-traumatic Stress Disorder among Peshmargas, Whom fought against ISIS War in Kurdistan Region Borders - Shireen J. Mohammed; Hoshyar A. Ahmed (Polytechnic Journal)
Background and objectives: Psychological disturbance is one of the most significant feature amongst individuals who are served military tasks. This study presented the Post Traumatic Disorder (PTSD) among the peshmargas (Kurdish military personnel) who joined in ISIS war. The aim of this study is to determine the prevalence of post-traumatic stress disorder among peshmargas returning from war and to identify the associated factors of PTSD among the study sample. Methods: A purposive sample of 113 peshmargas had been studied during the period 1st of January to 1st of June 2018. The participants’ responses to the PTSD Checklist had been recorded by the researchers. Results: The study revealed that 21.24% of peshmargas suffered from some symptoms of PTSD, more than half (52.21%) of them suffered from moderately to moderately high severity symptoms, and (26.55%) of them suffered from high severity of PTSD. It has been concluded that the high prevalence of PTSD among peshmargas needs attention from the concerned health institutions Conclusions: Evidence based research on treatment of PTSD among combat soldiers is neglected internationally. Most studies are needed to diagnosis the PTSD and other Psychological and Psychiatric disorder among non-deployed and deployed Peshmargas. Further research is needed to study the impact of positive PTSD on the psychosocial aspect of Peshmargas.